Pendistribusian Bantuan dan Penyuluhan Efisiensi Penggunaan Minyak Goreng Para Pelaku Sektor Informal Sentra PKL Semolowaru Surabaya - Suprijati, Jajuk; Sayidah, Nur; Listyaningsih, Listyaningsih; Zuraidah, Safrin; Tyas, Alvy Mulyaning (Universitas Nusantara PGRI Kediri, 2023)
The increase in cooking oil prices hit the household sector or the informal sector of small traders or street vendors (PKL). The COVID-19 pandemic has caused a decrease in income due to lonely customers plus a very high increase in cooking oil prices causing street vendors to get worse. This condition, of course, needs help from the community to find solutions to the problems faced by street vendors. The East Java Islamic Women Regional Leaders in collaboration with the Women's Organizational Cooperation Agency (BKOW) of East Java Province provide free cooking oil assistance to street vendors. The implementation of this activity is at the Semolowaru PKL Center, Surabaya, where the target of this activity is the informal sector actors, namely Street Vendors. The purpose of this activity is (1) to help the informal sector actors, namely Sentra PKL Semolowaru Surabaya, to carry out their business activities, while waiting for government policies in an effort to reduce cooking oil prices. (2) Provide services to the community that support the implementation of general government and development tasks.). The method used in the implementation of this community service is the method of partnering and collaborating with the BKOW (Women's Organizational Cooperation Agency) of East Java Province which can provide cooking oil with the price is cheap. The result of this activity is that the street vendors feel happy and are very helped so they want this activity to be carried out more often.